2022
DOI: 10.1128/aem.01600-22
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Models Suggest That On-Farm Noncrop Vegetation Removal Is Not Associated with Improved Food Safety Outcomes but Is Linked to Impaired Water Quality

Abstract: Currently, on-farm food safety decisions are typically made independently of conservation considerations, often with detrimental impacts on agroecosystems. Comanaging agricultural environments to simultaneously meet conservation and food safety aims is complicated because farms are closely linked to surrounding environments, and management decisions can have unexpected environmental, economic, and food safety consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…A 2020 review of agricultural water in the Southeastern United States noted that the geographical location of a water source played an important role in the prevalence and survival of foodborne pathogens ( 35 ). This conclusion is supported by other studies that compared microbial water quality between growing regions nationally ( 16 , 37 ) and locally ( 12 , 17 , 38 ), and between water types ( 32 , 39 41 ). Indeed, multiple studies have shown that this variability in water quality limits the efficacy of one-size-fits-all approaches to monitoring and mitigating microbial hazards in aquatic environments.…”
Section: Introductionsupporting
confidence: 77%
“…A 2020 review of agricultural water in the Southeastern United States noted that the geographical location of a water source played an important role in the prevalence and survival of foodborne pathogens ( 35 ). This conclusion is supported by other studies that compared microbial water quality between growing regions nationally ( 16 , 37 ) and locally ( 12 , 17 , 38 ), and between water types ( 32 , 39 41 ). Indeed, multiple studies have shown that this variability in water quality limits the efficacy of one-size-fits-all approaches to monitoring and mitigating microbial hazards in aquatic environments.…”
Section: Introductionsupporting
confidence: 77%
“…At least 32% of leafy green growers in California's Central Coast reported removing non-crop vegetation on their farms in a survey following the 2006 E. coli outbreak (Beretti and Stuart, 2008). Nearly a decade after the incident, ∼45% of California produce growers still reported clearing vegetation to create or expand bare-ground buffers around their fields (Baur et al, 2016), despite evidence suggesting the practice is ineffective at mitigating food-safety risks (Karp et al, 2015;Sellers et al, 2018;Glaize et al, 2021;Weller et al, 2022). Thus, growers often perceive that hedgerows and windbreaks pose food safety risks in attracting and harboring wildlife, and additional supply chain requirements from processors or retailers may actually prohibit hedgerows in close proximity to crops like leafy greens (Carlisle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%